Finite element modelling and simulation of the multiscale crystalline structure of aluminium deposit produced by helium cold spray additive manufacturing - Qi, J.; Raoelison, R. N.; Li, J.; Rachik, M. (Technische Universität Dortmund, 2025)
This study addresses an experimental analysis with a multiscale modelling of a pure Aluminium deposit produced by helium cold spraying. The grain morphology and the crystallographic texture of the deposit revealed a significant grain refinement along with a formation of strong metallurgical bonding. Complementing the experiments, a two-part multiscale modelling framework is developed, integrating a simulation of the particle upon impact and a crystal plasticity finite element model for analysing the consolidation and deformation mechanisms across multiple scales. Using Johnson-Cook equations and coupled Eulerian-Lagrangian approach, the particle impact model effectively captures high velocity impact behaviour, deformation mechanisms, and thermal interactions at the particle-substrate interface. The influence of intergranular interactions and phase heterogeneities on the overall mechanical response, at the mesoscale level, is investigated. The crystal plasticity-based approach can simulate the behaviour of individual grains within a representative volume element (RVE), with a prediction of the anisotropic mechanical properties and stress-strain relationships between various grains. The results pave the way for a better understanding of the microstructural evolution and mechanical behaviour of Aluminium deposits produced by helium cold spraying.
Keywords: Cold Spray; Plasticity Simulation; Crystal; Additive Manufacturing; Aluminium; Modelling; Microstructure; 620; 670; Kaltspritzen; Mikrostruktur; Finite-Elemente-Methode; Rapid Prototyping <Fertigung>; Simulation; Aluminium; Kristallstrukturanalyse